Contribution of Learning Attitude to Writing Skills Exposition Discourse of Class XI Students Smk Negeri 1 Tanah Datar - Elvina A. Saibi Saibi Saibi; Aimifrina Aimifrina; Fitra Afrida Amna (Postgraduate School, Universitas Negeri Padang, 2020)
ABSTRACT This study aims to determine the contribution of learning attitudes and learning motivation to the writing skills of exposition students of class XI SMK Negeri 1 Batipuh. This research is a type of cor-relational research. The population of all students of class XI of SMK Negeri 1 Batipuh totaling 187 people and a sample of 65 students. The instruments of this research were questionnaire and performance test. The results of the validity of the student learning attitude questionnaire were declared valid and the results of the reliability test were used reliably / reliable. The technique of analyzing research data uses the Kolmogorov-Smirnov test, multiple correlation test, t test, F test, and the determinant coefficient formula. The results of this study are learning attitudes contribute to the writing skills of exposition discourse by 10.0%. The conclusion of the study is the attitude of learning provides a significant positive contribution and relationship to the writing skills of exposition discourse. Keywords : Learning Attitudes and Writing Skills